Transactive memory systems and team innovation: A curvilinear approach. Issue 5 (5th August 2014) - Peltokorpi, Vesa; Hasu, Mervi
Abstract : Purpose: – The purpose of this paper is to hypothesize a curvilinear relation between transactive memory systems (TMS) and team innovation by integrating diverging conceptual and research findings in TMS research. While increasingly argued to enhance team innovation, TMS also have negative effects on team processes and outcomes. Design/methodology/approach: – The authors tested the hypothesis through hierarchical linear regression analyses using data obtained from 124 technical research teams. Findings: – Logistic regressions support the hypothesis, showing an inverse U-shaped relationship between TMS and team innovation, measured by patents received. Research limitations/implications: – The average within team response rate was relatively low, and the findings are driven by a limited number of teams with patents. Practical implications: – The findings suggest that research teams with moderate levels of TMS are the most effective in terms of patents received. Originality/value: – To the best of the authors' knowledge, this is the first empirical study to link TMS to team innovation and to test the potential counterproductive effects of TMS on team innovation.